The post-conviction polygraph in forensic practice - Elliott, Elizabeth (2017)
The aim of this thesis is to examine the impact of polygraphy disclosure and recidivism (particularly for sex offenders), gain greater understanding of some of the psychological mechanisms involved, and, in the light of this, consider the value of its application in forensic settings.